2022
DOI: 10.1038/s41598-022-21803-2
|View full text |Cite
|
Sign up to set email alerts
|

A robust COVID-19 mortality prediction calculator based on Lymphocyte count, Urea, C-Reactive Protein, Age and Sex (LUCAS) with chest X-rays

Abstract: There have been numerous risk tools developed to enable triaging of SARS-CoV-2 positive patients with diverse levels of complexity. Here we presented a simplified risk-tool based on minimal parameters and chest X-ray (CXR) image data that predicts the survival of adult SARS-CoV-2 positive patients at hospital admission. We analysed the NCCID database of patient blood variables and CXR images from 19 hospitals across the UK using multivariable logistic regression. The initial dataset was non-randomly split betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The need for creating a risk tool based on the results of routine blood biomarkers and basic patient information that would ensure the best possible triage for COVID-19 patients led to the development of LUCAS, a COVID-19 mortality prediction calculator [ 33 ]. LUCAS uses patients’ lymphocyte count, urea and C-reactive protein, as well as their age and sex, to categorize them into different risk levels expressed as low, medium, high, and very high risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The need for creating a risk tool based on the results of routine blood biomarkers and basic patient information that would ensure the best possible triage for COVID-19 patients led to the development of LUCAS, a COVID-19 mortality prediction calculator [ 33 ]. LUCAS uses patients’ lymphocyte count, urea and C-reactive protein, as well as their age and sex, to categorize them into different risk levels expressed as low, medium, high, and very high risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…These calculators include multiple demographic, laboratory, and imaging variables with various areas under the curve (AUC) of 0.75 to 0.88. Among these calculators: LUCAS ( 45 ), 4-C Mortality Index ( 46 ), NEWS2 ( 47 ), and COVID-GRAM ( 48 ) have been developed in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…[41,129,131,206] Several studies have shown that lymphopenia occurs approximately in 20% of patients with mild and 80% with severe COVID-19. [207,208] It is also a prognostic marker of poor disease outcome. [130] Researchers have found that the direct injection 3.…”
Section: Alleviation Of Lymphopeniamentioning
confidence: 99%
“…[ 41,129,131,206 ] Several studies have shown that lymphopenia occurs approximately in 20% of patients with mild and 80% with severe COVID‐19. [ 207,208 ] It is also a prognostic marker of poor disease outcome. [ 130 ] Researchers have found that the direct injection of NK or T cells is a direct and effective method for alleviation of lymphopenia, which can enhance the immune clearance of SARS‐CoV‐2 in COVID‐19 patients, and relevant clinical trials are underway, as shown in Table 3 .…”
Section: Applications Of Cell‐based Biomaterials In Coronavirus Disea...mentioning
confidence: 99%